PENGARUH LATIHAN PASSING BAWAH TERHADAP KEMAMPUAN BERMAIN BOLA VOLI - Alghifary, Rezi; Simanjuntak, Sadrak; Halomoan, Putri Nailah; Zakarian, Ucok Nifandi; Sitanggang, Samuel; Endriani, Dewi; Sahputra, Ramlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of lower passing training on volleyball playing ability through a literature review approach. The issue of limited performance in volleyball is often associated with inadequate mastery of fundamental techniques, particularly lower passing. The purpose of this study is to analyze how lower passing exercises contribute to improving players' performance. The method employed is a qualitative literature review by analyzing relevant scientific articles published between 2020 and 2025. The findings indicate that lower passing training plays a significant role in enhancing ball control, accuracy, and player coordination during gameplay. These improvements directly impact the effectiveness of team performance. In conclusion, lower passing training is a crucial component that should be systematically implemented to support the development of volleyball playing skills.